2022
DOI: 10.1037/bul0000381
|View full text |Cite
|
Sign up to set email alerts
|

The kernel of truth in text-based personality assessment: A meta-analysis of the relations between the Big Five and the Linguistic Inquiry and Word Count (LIWC).

Abstract: The Linguistic Inquiry and Word Count (LIWC) is a popular closed-vocabulary text analysis software program that is used to understand whether individuals' use of linguistic categories (i.e., word categories, such as negative affect) depends on their personality traits. Here, we present the first meta-analysis of the relations between the Big Five personality traits and 52 linguistic categories of the English language. Across 31 eligible samples (n = 85,724), the results showed that (a) self-reported personalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 146 publications
0
11
0
Order By: Relevance
“…Additionally, the growing toolkit of NLP methods will continue to provide unique methods that serve particular research goals to varying degrees. For example, relatively simple word counting methods are generally more explainable, transparent, and scalable than more computationally intensive "black box" models like neural networks, providing great value to researchers interested in explanation over prediction of psychological phenomena (Koutsoumpis et al, 2022). However, such methods are generally noisier and provide less value for scholars who require greater accuracy to achieve more predictive or complex psychometric goals (Kjell et al, 2022;Yarkoni & Westfall, 2017).…”
Section: Generative Artificial Intelligence Methods and The Future Of...mentioning
confidence: 99%
“…Additionally, the growing toolkit of NLP methods will continue to provide unique methods that serve particular research goals to varying degrees. For example, relatively simple word counting methods are generally more explainable, transparent, and scalable than more computationally intensive "black box" models like neural networks, providing great value to researchers interested in explanation over prediction of psychological phenomena (Koutsoumpis et al, 2022). However, such methods are generally noisier and provide less value for scholars who require greater accuracy to achieve more predictive or complex psychometric goals (Kjell et al, 2022;Yarkoni & Westfall, 2017).…”
Section: Generative Artificial Intelligence Methods and The Future Of...mentioning
confidence: 99%
“…First, more attention is needed to establish the validity of these novel approaches for operationalizing personality. Although these efforts have begun (e.g., Eichstaedt et al, 2021; Koutsoumpis et al, 2022; Park et al, 2015), opportunities abound to discern the appropriateness and efficacy of AI and other computing algorithms as valid raters of personality. Several AI techniques show initial evidence of convergence with self-reported measures, despite concerns that early forms of this technology cannot discriminate adequately between traits (Phan & Rauthmann, 2021).…”
Section: Current Applications Existing Limitations and Future Researc...mentioning
confidence: 99%
“…Past research has demonstrated that this assumption holds in many cases, with speech and writing reflecting personality traits, sociodemographic characteristics, personal values, and moral concerns (Boyd et al, 2015 ; Matsuo et al, 2019 ; Schultheiss, 2013 ; Schwartz et al, 2013 ; Tausczik & Pennebaker, 2010 ). Textual measures have mostly been validated against self-reports, showing different levels of correlation on a range of internal states (Boyd et al, 2015 ; Kennedy et al, 2021 ; Koutsoumpis et al, 2022 ; Lykousas et al, 2019 ; Malko et al, 2021 ; Matsuo et al, 2019 ; Mozes et al, 2021 ; Pellert et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…This assumption underlies the gold standard of quantitative text analysis in the social sciences (Iliev et al, 2015 ; Nelson et al, 2021 ; Tausczik & Pennebaker, 2010 ), which involves defining theoretical concepts of interest (Kennedy et al, 2022 ) prior to the selection of a textual corpus which will be analyzed with the help of multiple trained human coders (Krippendorff, 2004a ). When the goal is inference on internal states, the assumption becomes more specific: external observers can use cues in verbal behavior to deduce individuals’ internal states (Koutsoumpis et al, 2022 ). On the one hand, understanding how certain states are reflected in language is a distinctly human ability (Iliev et al, 2015 ; Kennedy et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation